MPS 13-08 EXCESS ALDOSTERONE IS A CRITICAL DANGER SIGNAL FOR INFLAMMASOME ACTIVATION IN THE DEVELOPMENT OF RENAL FIBROSIS IN MICE. (September 2016) - Satoh, Minoru; Kadoya, Hiroyuki; Sasaki, Tamaki; Taniguchi, Shun'ichiro; Takahashi, Masafumi; Kashihara, Naoki
Abstract : Objective: High levels of aldosterone impair renal function by activating proinflammatory and profibrotic pathways. However, the molecular mechanism underlying aldosterone-induced inflammation and fibrosis is unknown. Inflammasome activation contributes to chronic kidney disease. We hypothesized that aldosterone induces renal tubulointerstitial inflammation and fibrosis by activating the inflammasome. Design and Method: We used ASC-deficient mice (ASCKO) to investigate the role of inflammasome, which ASC is a critical component of the inflammasomes. C57Bl/6 mice (WT) were used for control. All animals were received left uninephrectomy and given drinking water with 1% NaCl. The mice were divided into the following groups: WT-vehicle (WT-vehi), WT-Aldo (WT-Aldo; 0.25 mg/kg/day, osmotic pump), WT-Aldo treated with eplerenone (WT-Aldo + Eple; 100 mg/kg/day, gavage), ASCKO-vehicle (ASCKO-vehi), ASCKO-Aldo (ASCKO-Aldo). Three weeks after drug administration, mice were sacrificed. In vitro assay, we investigated the mitochondrial superoxide production by Aldo, which is a trigger of inflammasome activation. Results: Infusing wild-type mice with aldosterone caused tubulointerstitial damage, increased expression of inflammasome components, caspase-1 activation, and overproduction of interleukin-1β and interleukin-18. These changes were suppressed by eplerenone treatment in wild-type mice or in mice deficient in apoptosis-associated speck-like protein with a caspase-recruitment domain. Caspase-1-positive and F4/80-positive cells colocalized in the interstitium. Bone marrow transplantation using ASC-deficient mice indicated that inflammasome activation in macrophages mediated aldosterone-induced renal fibrosis. Interleukin-18 was detected in culture supernatants of macrophages treated with aldosterone, and mitochondria-derived reactive oxygen species activated the inflammasome in these macrophages. Conclusions: Our results indicate that exposure of macrophages to high levels of aldosterone resulted in the activation of inflammasomes via the mitochondria-derived reactive oxygen species. Thus, inflammasome activation in macrophages may serve as a new therapeutic target for chronic kidney disease.